PENGARUH KONDISI SOSIAL EKONOMI KELUARGA TERHADAP HASIL PEMBELAJARAN SISWA SDN NO. 101810 GUNUNG MANAON - Nurmaulidia Tanjung; Emy Hariati (Program Studi Pendidikan Guru Sekolah Dasar Universitas Nahdlatul Ulama Sumatera Utara, 2023)
This study aims to determine the influence of family socio-economic conditions on the learning outcomes of students at SDN No. 101810 Gunung Manaon. This research is a quantitative study using an ex post facto approach, which is causal associative in nature. Data were obtained through questionnaires given to 40 respondents. The variables studied include parental education level, family income, household asset ownership, and family needs/expenditure fulfillment. Data analysis was conducted using multiple regression with the help of SPSS Version 20 for Windows. The results showed that the father's education level did not affect students' learning outcomes, while the mother's education level, family income, household asset ownership, and family needs fulfillment had a positive and significant influence on students' learning outcomes. The contribution of all independent variables in explaining the dependent variable was 68.06%, with the remaining 31.94% explained by other variables outside the model.